Determining the influence of some factors on improving the quality of Sherry wine material - Fataliyev, Hasil; Gadimova, Natavan; Taghiyev, Azer; Baloghlanova, Konul; Alakbarov, Alakbar (Technology audit and production reserves, 2025)
The object of research is the production of Sherry must and wine materials, as well as the processes that occur during this production. Factors affecting the quality of Sherry wine material – particularly the amount of juice yield, different combinations of fining agents, the duration and course of fermentation, and the role of the grape variety – have not been sufficiently studied. It was found that increasing the juice yield per ton of grapes from 50 to 75 decaliters led to an increase in aldehydes from 61.2 mg/dm³ to 86.1 mg/dm³, esters from 67.3 mg/dm³ to 86.7 mg/dm³, higher alcohols by 40 mg/dm³, and terpenes by up to 100 mg/dm³ in the resulting wine material. An increase in phenolic compounds and oxidation-reduction potential (ORP) caused oxidation uncharacteristic of Sherry wine material, leading to a decrease in quality. Sensory analysis showed a decline in quality scores by 0.02–0.10 points. The effect of fining agents reduced the content of phenolic compounds and titratable acids, while color values shifted positively. Juice samples were fermented both with (experimental) and without (control) the addition of nutrient supplements. Compared with the control, fermentation in the experimental samples was completed 2 days earlier. Increasing the dose of sulfur dioxide added to the juice from 50 mg/dm³ to 120 mg/dm³ resulted in a decrease in alcohol content and an increase in titratable acidity in the fermented samples. Wine materials prepared from Bayan, Fetyaska, and Rkatsiteli grape varieties are suitable for Sherry production; however, in terms of optimal composition, Fetyaska wine material was considered superior. The obtained results can be applied in family-owned vineyards and winemaking enterprises.